2007
DOI: 10.1016/j.ygyno.2007.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Development of multimarker panel for early detection of endometrial cancer. High diagnostic power of prolactin

Abstract: Objective-Endometrial carcinoma is the most common gynecologic cancer. Although the prognosis for endometrial cancer is generally good, cancers identified at late stages are associated with high levels of morbidity and mortality. Therefore, prevention and early detection may further reduce the burden of this challenging disease.Methods-A panel of 64 serum biomarkers was analyzed in sera of patients with stages I-III endometrial cancer and age-matched healthy women, utilizing a multiplex xMAP ™ bead-based immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 45 publications
3
64
2
Order By: Relevance
“…Yurkovetsky et al identified that prolactin is a serum biomarker with sensitivity and specificity for EC. 15 They found that serum CA 125, CA 15-3 and CEA are higher in patients with Stage III disease when compared to Stage I, and a five-biomarker panel of prolactin, GH, eotaxin, E-selectin and TSH discriminated EC from ovarian and breast cancer. Nevertheless, none of these potential biomarkers has been validated nor reached the clinical practice.…”
Section: Early Detection and Diagnosismentioning
confidence: 98%
“…Yurkovetsky et al identified that prolactin is a serum biomarker with sensitivity and specificity for EC. 15 They found that serum CA 125, CA 15-3 and CEA are higher in patients with Stage III disease when compared to Stage I, and a five-biomarker panel of prolactin, GH, eotaxin, E-selectin and TSH discriminated EC from ovarian and breast cancer. Nevertheless, none of these potential biomarkers has been validated nor reached the clinical practice.…”
Section: Early Detection and Diagnosismentioning
confidence: 98%
“…Therefore, if the proper components of EBV antigens, such as EA-D and EBNA1, were selected, both xMAP and ELISA assays could have relatively high sensitivity, specificity, and AUC for EBV serodiagnosis of NPC. The flexibility of the xMAP technology as well as its throughput ability gives it broad applications, such as cytokine and chemokine analysis, antibody screening, HLA typing, pathogen detection, and single-nucleotide polymorphism or mutation analysis (1,4,8,9,19,25,36). Our results showed that the xMAP assay is suitable for EBV antibody detection when proper biomarkers are used and provides valid serological profiles of EBV in NPC patients.…”
Section: Discussionmentioning
confidence: 73%
“…For example, studies on prostate cancer and head and neck cancer concluded that there was no correlation between PRL levels and cancer risk (18,19). However, Yurkovetsky et al showed that PRL was the strongest discriminative biomarker for endometrial cancer (20).…”
Section: Discussionmentioning
confidence: 99%